PERAN ENTREPREUNERIAL MARKETING DALAM MENGHADAPI TANTANGAN PENCAPAIAN PENDAPATAN DI HOTEL CIPUTRA SEMARANG - Kusmastuti, Erny; Indrianto, Agoes Tinus Lis (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Abstract. This study examines the importance of entrepreneurial marketing in Hotel Ciputra Semarang, with a focus on the use of entrepreneurial marketing dimensions and their impact on hotel revenue. The research method used is descriptive qualitative with triangulation analysis, focusing on execution, management, and hotel staff as respondents. Data are collected through surveys and detailed observations. The study's findings on entrepreneurial marketing, particularly in the context of a competitive business environment, have a positive impact on Hotel Ciputra Semarang by providing different perspectives and diversifying marketing strategies. This study identifies the role of entrepreneurial marketing in providing guidance to hotel practitioners on how to improve management strategies and effectively manage time, hence providing guidance to businesses seeking to optimize their revenue generation.